From Lebanese Soil to Antimicrobials: A Novel Streptomyces Species with Antimicrobial Potential - Razane Hamiyeh; Aya Hanna; Antoine Abou Fayad (Fermentation, 2025)
The ongoing threat of antimicrobial-resistant pathogens has intensified the need for new antimicrobial agents, making the discovery of novel natural products crucial. This study focuses on the isolation and characterization of a novel Streptomyces species from the Anjar region in Lebanon, an area rich in microbial diversity that is largely unexplored for its biotechnological potential. Soil samples were collected and processed, leading to the isolation of Streptomyces strain ANJ10. Comprehensive morphological, physiological, and genomic analyses were conducted, including whole-genome sequencing (WGS) to identify biosynthetic gene clusters (BGCs) and broth microdilution (BMD) assays to evaluate antimicrobial activity. The ANJ10 genome revealed 42 BGCs, significantly more than the average number in Streptomyces species, suggesting a high potential for secondary metabolite production. Phylogenetic analysis confirmed ANJ10 as a novel species, and BMD assays demonstrated its strong antimicrobial activity against several gram-negative pathogens, specifically, Acinetobacter baumannii. These findings underscore the potential of this strain as a significant source of new antimicrobial compounds, reinforcing the importance of exploring underexploited environments like Lebanon for microbial bioprospecting.